(untitled) (Teología, 2019)
During the development of Vatican II, the systematic form in which thought and belief should shape each other was the object of important debates, specifically due to the novelty represented by the introduction of the inductive method in ecclesiastical teaching. It was realized that this innovation included a challenging reflection about the Church’s self-understanding, and therefore a crucial debate about the goals of the Council itself. Such method, which later on was questioned, has been particularly relevant in the Latinamerican post Council. Today, at stake are the chances that the Church, faith and theology become less indifferent to the unease that emerges from the complex biographic experiences and to the outcry that bursts out of the world of suffering and from the poor.